The schematic structure in oral case presentation of ESL medical students - Abdul Malik, Faridah; Yaakob, Nor Hasni (American Scientific Publishers, 2018)
Due to the importance of oral case presentation in the pedagogical assessment of medical students and for their future career as medical officers, this study attempted to investigate the rhetorical pattern of oral case presentations of Clinical undergraduates of Year 3 and Year 5 at the International Islamic University Malaysia. Using content analysis, and proposed sampling, 32 case presentations were recorded during ward rounds and analysed. The researcher mapped all recordings against Dell, Lewin and Gigante’s Oral Presentation Expectations Checklist, and found that the subjects did not adhere to the schematic structure identified.